On the localization Eigenfunction expansions associated with the Schrodinger Operator - Rakhimov, Abdumalik (IDOSI Publications, 2013)
In this paper we study eigenfunction expansions associated with the Schrodinger operator with a singular potential. In the paper it is obtained sufficient conditions for localization and uniformly convergence of the regularizations of the corresponding expansions